Obesity-induced dysbiosis exacerbates ifn-γ production and pulmonary inflammation in the mycobacterium tuberculosis infection - Palma Albornoz, Sandra Patricia; Fraga-Silva, Thais Fernanda de Campos; Gembre, Ana Flávia; de Oliveira, Rômulo Silva; de Souza, Fernanda Mesquita; Rodrigues, Tamara Silva; Kettelhut, Isis Do Carmo; Manca, Camila Sanches; Jordao, Alceu Afonso; Ramalho, Leandra Naira Zambelli; Ribolla, Paulo Eduardo Martins [UNESP]; Carlos, Daniela; et al. (MDPI, 2021)
The microbiota of the gut–lung axis affects local and far-reaching immune responses and might also trigger chronic and inflammatory diseases. We hypothesized that gut dysbiosis induced by obesity, which coexists in countries with a high tuberculosis burden, aggravates the host susceptibility and the pulmonary damage tolerance. To assess our hypothesis, we used a model of high-fat diet (HFD)-induced obesity, followed by infection of C57BL/6 mice with Mycobacterium tuberculosis. We showed that obesity increased the susceptibility, the pulmonary inflammation and IFN-γ levels in M. tuberculosis-infected mice. During the comorbidity obesity and tuberculosis, there is an increase of Bacteroidetes and Firmicutes in the lungs, and an increase of Firmicutes and butyrate in the feces. Depletion of gut microbiota by antibiotic treatment in the obese infected mice reduced the frequencies of CD4+ IFN-γ+ IL-17− cells and IFN-γ levels in the lungs, associated with an increase of Lactobacillus. Our findings reinforce the role of the gut–lung axis in chronic infections and suggest that the gut microbiota modulation may be a potential host-directed therapy as an adjuvant to treat TB in the context of IFN-γ-mediated immunopathology.
Keywords: Gut–lung axis; Microbiota; Obesity; Tuberculosis